Utility of Screening for Obstructive Sleep Apnea in Cardiac Rehabilitation. Issue 6 (November 2016) - Marzolini, Susan; Sarin, Michael; Reitav, Jaan; Mendelson, Monique; Oh, Paul
Abstract : PURPOSE: Obstructive sleep apnea (OSA) is prevalent in patients with cardiovascular disease and is often undiagnosed. The purpose of this study was to determine the utility of communicating OSA risk with the patients in a diabetes and cardiac rehabilitation program (CRP) and primary care physicians. METHODS: Following an OSA education session, 295 patients in diabetes and CRPs were screened for OSA and daytime sleepiness by STOP-BANG and Epworth Sleepiness Scale questionnaires. Letters were sent to patients at high risk or noncompliant with continuous positive airway pressure (CPAP) treatment and their physicians. Follow-up questionnaires were sent to patients 6 months later. RESULTS: Of the 295 patients screened, 16.6% (n = 49) had an OSA diagnosis and had been prescribed CPAP. A smaller proportion patients in the diabetes program than in the CRP had discontinued CPAP (22.2% vs 45.2%; P = .03) with discomfort being the greatest barrier. Three of the 7 patients (42.9%) who had contact with their physician resumed CPAP. Of the remaining 246 patients who scored high on ≥1 questionnaire (77.6%; n = 191) and returned the 6-month questionnaire (53.9%; n = 103), communication of risk assessment resulted in 49.5% (n = 51) of patients consulting with their physician. Of those, half were referred for polysomnography. All were diagnosed with OSA. CONCLUSION: More than three quarters of patients in diabetes and CRPs scored high on ≥1 questionnaire suggesting signs/symptoms of OSA. However, only 16.6% were prescribed CPAP and compliance to treatment was poor (63.3%). Education and communication of OSA risk with patients and physicians resulted in a de novo diagnosis in at least 1 of 10 patients screened and 16.7% restarted CPAP. Abstract : Cardiac rehabilitation programs provide an opportunity to identify risk for obstructive sleep apnea. Patients (n = 295) were screened for obstructive sleep apnea using questionnaires. Patients previously prescribed continuous positive airway pressure (16.6%) had poor compliance to treatment (63.3%). Education and communication with patients and physicians resulted in a new diagnosis in 1 of 10 patients screened and 16.7% restarting continuous positive airway pressure.